USING FIGURATIVE LANGUAGE IN COSMETIC ADVERTISEMENTS ON INDONESIAN TELEVISION - Mastura Sofyan; Zulfadli A. Aziz; Bukhari Daud (Universitas Syiah Kuala, 2020)
Advertisement is one of the essential types of mass communication expected to persuade people to buy products or services. In advertisement, language use should be persuasive because it intends to influence the customers to purchase the items. Using figurative expression in advertisement is one way to attract consumers ‘attention. This qualitative research was aimed at finding out the types of figurative expression and its function used in cosmetic advertisements advertised on Indonesian television. The data of this research were the cosmetic advertisements showed on Indonesian television in 2018 that employed English figurative expression in slogan of the advertisement. From 23 data identified, the researchers found that all of them deployed figurative expressions in various types. The most dominant figurative expression found in this research was hyperbole. It was found that out of 23 advertisements, twelve of advertisements used hyperbole expression, whereas personification expression was found in one advertisement. Besides, the researchersfound five advertisements using repetition expression, two advertisements employing metaphor expression, two slogans of advertisement using simile expression, and one parallelism expression found in advertisement.